A Facile "Double‐Catalysts" Approach to Directionally Fabricate Pyridinic NB‐Pair‐Doped Crystal Graphene Nanoribbons/Amorphous Carbon Hybrid Electrocatalysts for Efficient Oxygen Reduction Reaction. Issue 13 (17th February 2022) - Fan, Mengmeng; Yuan, Qixin; Zhao, Yuying; Wang, Zeming; Wang, Ao; Liu, Yanyan; Sun, Kang; Wu, Jingjie; Wang, Liang; Jiang, Jianchun
Abstract: Carbon material is a promising electrocatalyst for the oxygen reduction reaction (ORR). Doping of heteroatoms, the most widely used modulating strategy, has attracted many efforts in the past decade. Despite all this, the catalytic activity of heteroatoms‐modulated carbon is hard to compare to that of metal‐based electrocatalysts. Here, a "double‐catalysts" (Fe salt, H3 BO3 ) strategy is presented to directionally fabricate porous structure of crystal graphene nanoribbons (GNs)/amorphous carbon doped by pyridinic NB pairs. The porous structure and GNs accelerate ion/mass and electron transport, respectively. The N percentage in pyridinic NB pairs accounts for ≈80% of all N species. The pyridinic NB pair drives the ORR via an almost 4e − transfer pathway with a half‐wave potential (0.812 V vs reversible hydrogen electrode (RHE)) and onset potential (0.876 V vs RHE) in the alkaline solution. The ORR catalytic performance of the as‐prepared carbon catalysts approximates commercial Pt/C and outperforms most prior carbon‐based catalysts. The assembled Zn–air battery exhibits a high peak power density of 94 mW cm −2 . Density functional theory simulation reveals that the pyridinic NB pair possesses the highest catalytic activity among all the potential configurations, due to the highest charge density at C active sites neighboring B, which enhances the interaction strength with the intermediates in the p‐band center. Abstract : The dominantly pyridinic NB pair is rationally fabricated on hierarchically structure of crystal graphene nanoribbons/amorphous carbon by a "double‐catalysts" strategy. As experiments and density functional theory demonstrated, the pyridinic NB plays a key role for the highly catalytic performance (half‐wave potential, 0.812 V vs reversible hydrogen electrode, electron transfer number, ≈3.94), comparable to commercial Pt/C and superior to most of carbon‐based electrocatalysts.